Towards a new model of environmental management - Prado Román, Camilo; Blanco González, Alicia; Díez Martín, Francisco (Observatorio Medioambiental, 2011)
Prospective analysis brought us closer to the future on the basis of the current reality. This analysis advised us that environmental management is used, generated and developed, only if it supports the interests of the organization. Using prospective structural models, we have developed an environmental management model for the future by establishing the most influential and most dependent variables. Research shows that direct action objectives of environmental management processes lose their finalist character over time, turning it into objectives linked to excellence: quality, environment and social responsibility.
Keywords: Environmental Management; Prospective Studies.